Gambaran Pola Konsumsi Fast Food dan Status Gizi Siswa di SMP Negeri 10 Denpasar - Ayu Suantari, Ni Putu; Wiardani, SST, M.Kes, Dr. Ni Komang; Agustini, SKM, M.Si, Ni Putu (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2025)
Teenagers are more influenced by the environment and lifestyle. Many teenagers eat outside the home and are greatly influenced in their food choices. Teenagers often try new foods, one of which is fast food. The purpose of this study was to determine the description of fast food consumption patterns and nutritional status of students at SMP Negeri 10 Denpasar. The type of research used in this study was observational with a cross-sectional research design and measurements of body weight and height were carried out and students were interviewed about fast food consumption patterns. The number of samples in this study was 38 students. The results of the observation showed that the characteristics of students based on gender were mostly female, as many as 23 samples (60.53%) and most students were 15 years old, as many as 23 students (60.53%). The nutritional status of students was 7.89% of students with malnutrition status, 71.05% of students with normal nutritional status, 7.89% of students with overweight status and 13.16% of students with obesity nutritional status. There are 71.05% of students who consume fast food in the category of little, 73.68% of students often consume fast food and most students have an average consumption of macronutrients in fast food above average. Students with above average consumption of energy, protein, fat and carbohydrates in fast food tend to have obesity nutritional status. It is hoped that schools can work together to help reduce students' consumption of fast food by building a healthy canteen, and working together with the school's UKS in providing education about the impact of consuming fast food in the long term and to students of SMP Negeri 10 Denpasar to bring school supplies to reduce fast food consumption in each classification of nutritional status, especially for students who have overweight and obesity nutritional status.